CLINICAL OBSERVATION OF THE USE OF ORAL VINORELBINE IN THE TREATMENT OF DISSEMINATED ESTROGEN-RECEPTORPOSITIVE, HER2-NEGATIVE BREAST CANCER - Xudoyorov M.S; Jabborov J.Sh; Yakubova D.T. (Scholar Express Journal, 2022)
Fresh water supply is a major challenge to agriculture in semi-arid zones and deep groundwater pumping for irrigation is applied widely in such regions to span droughts. However, climate change and overexploitation of groundwater reservoirs foster instability and qualitative degradation of aquifers, thus adaptation measures to increasing water scarcity such as the construction of fresh water reservoirs from surface runoff were applied during the last decades. Small-scale retention basins seem to be ecologically more appropriate in comparison to large dam systems, as construction of large dams causes deforestation and harmful impacts on wildlife. In this context, the ways of controlling and monitoring of water will be discussed
Keywords: Breast Cancer; Disseminated; HER2-Negative; Estrogen